Evidence-based assessment of male-only infertility: prevalence and associated risk factors in Port Harcourt metropolis, Rivers State, Nigeria - Elekima, Ibioku; Aworu, Aminayanate M.; Brown, Holy; Brisibe, Ngozi; George-Opuda, Ibitoroko M.; Waribo, Helen A.; Ben-Chioma, Adline E.; Bartimaeus, Ebirien-Agana S. (International Journal of Research in Medical Sciences, 2023)
Background: Male infertility is the condition in which a male is unable to establish pregnancy in a fertile woman over 12 months of unprotected sexual intercourse. In this study, the prevalence of male-factor infertility and some associated risk factors in Port Harcourt, Rivers State was carried out. Methods: The study design was a case-controlled randomized one, in which semen specimens were collected from case and control groups randomly amongst males visiting urology/fertility clinics by masturbation after 3 days of abstinence. A total of 276 males indicated interest to participate in study of which 193 male subjects were recruited. Results: The result showed that 20.8% were azoospermic, 27.4% were oligospermic, 23.7% were asthenozoospermic, 27.9% oligoasthenozoospermic, 15.1% teratozoospermic, 19.4% asthenoteratozoospermic, and 12.9% oligoasthenoteratospermic. Furthermore, the microbial quality of the semen assessed indicated the prevalence of scanty, moderate, and heavy growth as 12.5%, 9.3%, and 7.3% respectively. Likewise, organisms isolated and identified were Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae, and mixed growth of staphylococcus aureus, and Escherichia coli with a prevalence of 18.2%, 5.6%, 2.0%, 1.04%, and 2.6% respectively. Civil servants had the highest prevalence of 20.8% followed by artisans with 11.9%. The prevalence of primary and secondary infertility was observed to be 30.1% and 18.1% respectively. Conclusions: Male-only factor infertility is on the increase and occupations that are accompanied by prolonged sitting, sedentary work style, or working in or close to high-temperature sources as seen in civil servants and welders (artisans) were observed to be more prone to male-only factor infertility.